The European Union and the Technology Shift
XI, 264 p. 5 illus.
Keywords: ‘This volume has a solid foundation in the highly topical question of technological change. More importantly, the individual chapters are written by qualified scholars whose analytically advanced contributions are likely to interest a wide audience. I can strongly recommend this book for scholars and students in political science, law, and economics.’ —Carl Fredrik Bergström, Professor of European Law, Uppsala University, Sweden ‘As the digital transformation affects every single one of us it is important that we have the widest possible debate on its inherent risks and opportunities, and how these are shared across society. This is why I warmly recommend this volume: because it brings together an inter-disciplinary set of scholars able to analyse the multifaceted implications of the technological shift. I could not agree more with the book’s main takeaway, i.e. that we need to create an adaptive regulatory framework capableof harnessing the positive effects of technological changes while buttressing the negative impact on European society and citizens.’ —Ambassador Kim Jørgensen, Head of Cabinet to Commissioner and Executive Vice-President Margrethe Vestager, European Commission This book explores the multiple challenges that the global technology shift is posing to the EU. From the vantage point of experts from economics, law, and political science, this book provides insights into the role that the EU is and ought to be playing in regulating global platform companies, addressing taxation in the digital economy, mitigating job displacements on the labour market, and tackling ethical concerns of artificial intelligence and the prospect of digital democracy. All chapters are based on up-to-date research findings and succinct assessment of ongoing debates. They conclude with policy recommendations for policy makers on European and national levels. Antonina Bakardjieva Engelbrekt is Professor of European Law in the Faculty of Law, Stockholm University, Sweden. Karin Leijon is a researcher in the Department of Government, Uppsala University, Sweden. Anna Michalski is Associate Professor in Political Science in the Department of Government, Uppsala University, Sweden. Lars Oxelheim is Professor of International Business and Finance at the University of Agder, Norway, and affiliated with the Research Institute of Industrial Economics (IFN), Sweden.